Non-Puerperal Inversion of the Uterus Caused by Prolapsed Leiomyoma - Koirala, Sagar; Rana, Ashma; Gurung, Geeta; Baral, Josie; Pokharel, Sita; Giri, Smith (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v5i2.5080 NJOG 2010 Nov-Dec; 5(2): 48-49